ECONOMIC EFFICIENCY OF AGROTERNIAL MEASURES FOR GROWING MEXICAN DATURA INNOXIA (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2026)
Fertilization of Datura innoxia is used to provide it with nutrients throughout its growth period, especially during the period of high demand for nutrients: budding and flowering. The main part of the planned fertilizer rate of basic fertilizers is introduced into the soil. Depending on the soil-climatic conditions of the place where the plant is planted and some economic and organizational problems, basic fertilization is carried out more often in autumn, and in some cases in spring. This article presents information on the economic efficiency of agrotechnical measures for growing Datura innoxia.